2007
DOI: 10.1093/europace/eum176
|View full text |Cite
|
Sign up to set email alerts
|

Biventricular ICD implant using endocardial LV lead placement from the left subclavian vein approach and transseptal puncture via the transfemoral route

Abstract: We present the case of a 72 years old diabetic male patient with severe dilated ischaemic cardiomyopathy and New York Heart Association functional class III symptoms and previous unsuccessful attempts to cardiac resynchronization therapy using the conventional epicardial left ventricular (LV) pacing through the coronary sinus. He also had an indication for ICD implantation. We successfully implanted a biventricular ICD system from the standard left subclavian vein approach using endocardial placement of the LV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 3 publications
0
28
0
Order By: Relevance
“…17 The atrial transseptal approach to LV endocardial pacing was initially described by Jaïs et al 10 Modifications of the technique have been developed for the past decade, but it remains complex, with a combined inferior and superior approach used to puncture the atrial septum and deliver a lead from the subclavian vein. [9][10][11][12][13] Balloon dilatation of the septum and the use of snares to feed guidewires or pacing leads across into the left atrium is a common feature. [9][10][11][12][13] In the present study, all patients had a successful procedure using only the upper chest venous access site, reducing complexity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 The atrial transseptal approach to LV endocardial pacing was initially described by Jaïs et al 10 Modifications of the technique have been developed for the past decade, but it remains complex, with a combined inferior and superior approach used to puncture the atrial septum and deliver a lead from the subclavian vein. [9][10][11][12][13] Balloon dilatation of the septum and the use of snares to feed guidewires or pacing leads across into the left atrium is a common feature. [9][10][11][12][13] In the present study, all patients had a successful procedure using only the upper chest venous access site, reducing complexity.…”
Section: Discussionmentioning
confidence: 99%
“…8 Several variations of a percutaneous atrial transseptal route for LV endocardial pacing have also been described, but all are complex, expose a significant length of the lead to the systemic circulation, and may potentially interfere with mitral valve function. [9][10][11][12][13] Access to the LV endocardium through the interventricular septum may offer a simpler and more direct route for CRT. We have previously described LV endocardial pacing via the transinterventricular septal route in 1 patient.…”
Section: Clinical Perspective On P 22mentioning
confidence: 99%
“…Another group has described a method using direct TS puncture from the left axillary vein [18]. In 2007 Van Gelder et al and Nuta et al described successful endocardial LV lead placement from the subclavian vein into the LV cavity via the interatrial septum, following transseptal puncture through the femoral vein to allow entry of the LV lead from above [15,16]. In our patients, we used the latter approach.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with advanced heart failure, this approach may be linked with a high morbidity and mortality. Endocardial LV lead placement through an atrial transseptal approach has been described previously as an alternative technique to provide CRT in cases where epicardial LV lead implantation is contraindicated or is at increased risk [12][13][14][15][16][17][18]. In the following paper we describe the technique that we used and the outcomes of the transseptal endocardial LV implant in patients for whom transvenous CS lead placement had failed and are not eligible for surgical epicardial implantation and have no contraindication for lifelong oral anticoagulation.…”
Section: Introductionmentioning
confidence: 99%
“…As trial. The atrial transseptal approach has also been reported; [49][50][51] however, this technique has been limited by technical difficulties with the procedure. Overall, although LV endocardial pacing is promising for those with those patients in whom LV lead placement is not possible or CS anatomy does not provide an optimal branch location there…”
Section: Alternate Approaches To Left Ventricular Lead Placementmentioning
confidence: 99%